Dakwah Kebangsaan : Implementasi Nilai-Nilai Pncasila di Perguruan Islam Pondok Tremas Pacitan - Ilahiyah, Nafahatul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The study will discus about urgency of pancasila’s values in the context of life. The role of islamic boarding schools has has proven to be effective as a media for dak’wah in implementing the values of pancasila. The phenomenon that has occured among today’s young people is very disturbing, so that if it is not fortified with religious values and Pancasila as the basis of the Indonesia state the foundation for future generations will be destroyed. Pondok Tremas is one of the islamic pesantren that consistently internalizes the values of pancasila. Apart from the religious knowledge taught at Pondok Tremas, general science is also taught there, one of which is civics. This research is a type qualitative research with a field reserach metode and uses data collection techniques by means of obervation and interviews. Explicitly, Tremas Islamic pesantren instilling pancasila is devided into three things, namely formal education curriculum, non-formal education, and field activities.the results of this research show that the world of islamic peantren has given birth to a generation that is anti-radicalist and terrorist by balancing the cultivation of religious knowledge and Pancasila values.